2014
DOI: 10.1080/09658211.2014.986135
|View full text |Cite
|
Sign up to set email alerts
|

Auditioning the distinctiveness account: Expanding the production effect to the auditory modality reveals the superiority of writing over vocalising

Abstract: The production effect (PE) documents the advantage in memory performance for words that are read aloud during study, rather than words that are read silently. Until now, the PE was examined in the visual modality, as the participants read the study words. In the present study, we extended the PE phenomenon and used the auditory modality at study. This novel methodology provides a critical test of the distinctiveness account. Accordingly, the participants heard the study words and learned them by vocal producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…2014, p. 509). Since their initial study in 2010, multiple studies have reported similar findings with adults in behavioral research (Fawcett, 2013;Kaushanskaya & Yoo, 2011;Mama & Icht, 2016;MacLeod, 2011;Zamuner, Morin-Lessard, Strahm, & Page, 2016, among others) and neurophysiological research (Mathias, Palmer, Perrin, & Tillmann, 2015). The production effect is strongest in within-subject designs (Fawcett, 2013), and there are studies showing no effect of production in between-subjects designs (e.g., Abbs, Gupta, & Khetarpal, 2008).…”
mentioning
confidence: 86%
“…2014, p. 509). Since their initial study in 2010, multiple studies have reported similar findings with adults in behavioral research (Fawcett, 2013;Kaushanskaya & Yoo, 2011;Mama & Icht, 2016;MacLeod, 2011;Zamuner, Morin-Lessard, Strahm, & Page, 2016, among others) and neurophysiological research (Mathias, Palmer, Perrin, & Tillmann, 2015). The production effect is strongest in within-subject designs (Fawcett, 2013), and there are studies showing no effect of production in between-subjects designs (e.g., Abbs, Gupta, & Khetarpal, 2008).…”
mentioning
confidence: 86%
“…Vocalization was found to enhance memory for various types of materials, such as pictures (Icht and Mama, 2015), nonwords (MacLeod et al, 2010, Expt 6), sentences and text (Ozubko et al, 2012), and across different populations (e.g., older adults, Lin and MacLeod, 2012;children, Icht and Mama, 2015). Recently, the PE was expanded to the auditory modality, which involves the learning of aurally presented words (rather than written words; Mama and Icht, 2016a).…”
Section: The Pe In Memorymentioning
confidence: 99%
“…The production that involves the greater number of unique encoding processes leads to the best memory (Mama and Icht, 2016b). Producing a word results in a quantitative as well as qualitatively different memory record than no-production, such as silent reading or listening (Putnam et al, 2014;Mama and Icht, 2016a); at retrieval, participants are able to use this distinctive information as part of their decision process to guide test performance (Fawcett et al, 2012) in favor of the produced words.…”
Section: The Pe In Memorymentioning
confidence: 99%
“…pictures (Icht and Mama, 2015). It was also found for auditory-presented words (Mama and Icht, 2016a;Taitelbaum Swead et al, 2017). Many populations show a PE, from preschool children (Icht and Mama, 2015) to younger and older adults (Lin and MacLeod, 2012).…”
mentioning
confidence: 77%
“…Encoding distinctiveness has been also interpreted from a quantitative perspective, by the number of distinct encoding processes that take place at study. The greater their number, the higher the memory benefit (Forrin et al, 2012;Mama and Icht, 2016a). In other words, the production that includes more distinct, nonoverlapping processes provides a larger boost to memory.…”
mentioning
confidence: 99%